1952
DOI: 10.1007/bf02640170
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of styrene in the presence of fatty acid methyl esters

Abstract: SummaryData on the products obtained on polymerizing styrene in the presence of various methyl esters of fatty acid have been presented. These data show that no copolymerization between the esters and styrene occurs and that homogeneity of some of the reaction products cannot be considered as proof for interpolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1953
1953
1977
1977

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Since this is true, polymers made with high proportions of benzoyl peroxide would be expected to show higher saponification values. In general, this was what was observed by Falkenburg et al (7,8).…”
Section: Analysis Of Polymers Brunner and Tuckersupporting
confidence: 90%
See 1 more Smart Citation
“…Since this is true, polymers made with high proportions of benzoyl peroxide would be expected to show higher saponification values. In general, this was what was observed by Falkenburg et al (7,8).…”
Section: Analysis Of Polymers Brunner and Tuckersupporting
confidence: 90%
“…Contrary to the results of Petit and Fournier (15), Schroeder and Terrill (17) found that both raw and blown linseed oil combined with styrene under polymerization conditions. Falkenburg, Hill, and Wolff (7,8) studied the reaction of styrene with oils as well as with methyl esters of most of the common fatty acids. They concluded that styrene did not copolymerize with the esters and that homogeneity of the product was no criterion of copolymerization.…”
mentioning
confidence: 99%
“…These various catalysts indicate the possibility of preparing homopolymers of the drying oils by means of normal free-radical and ionic catalysts. The preparation of copolymers of drying oils with such a reactive monomer as styrene can also be attained, in spite of references in the literature to the contrary (55). For instance, by the use of benzoyl peroxide, the copolymeri-zation of styrene with the methyl esters of a number of different fatty acids has been successfully initiated.…”
Section: B Other Catalystsmentioning
confidence: 99%